Addressing the Right Targets in Oncology: Challenges and Alternative Approaches. (March 2015) - Stock, Julie K.; Jones, Neil P.; Hammonds, Tim; Roffey, Jon; Dillon, Christian
Translating existing and emerging knowledge of cancer biology into effective novel therapies remains a great challenge in drug discovery. A firm understanding of the target biology, confidence in the supporting preclinical research, and access to diverse chemical matter is required to lower attrition rates and prosecute targets effectively. Understanding past successes and failures will aid in refining this process to deliver further therapeutic benefit to patients. In this review, we suggest that early oncology drug discovery should focus on selection and prosecution of cancer targets with strong disease biology rather than on more chemically "druggable" targets with only modest disease-linkage. This approach offers higher potential benefit but also increases the need for innovative and alternative approaches. These include using different methods to validate novel targets and identify chemical matter, as well as raising the standards and our interpretation of the scientific literature. The combination of skills required for this emphasizes the need for broader early collaborations between academia and industry.